1025 Readmission & Mortality Rates Following Enhanced Recovery After Surgery (ERAS) For Colorectal Procedures at An Island DGH. (4th May 2021) - Moore, P; Pickering, O; Cook, E
Abstract: Introduction: Colorectal surgery under ERAS reduces postoperative morbidity by 40-50% and shortens length of hospital stay by 2-3 days. The 2018 National Bowel Cancer Audit reported a 30-day readmission rate of 10.5% for colorectal surgery under ERAS and a 90-day mortality rate of 2% nationally. Evidence shows readmission rates increase with discharge C-reactive protein (CRP); 16.5% when CRP >100 mg/L and 6% when CRP <100 mg/L. Method: Data was collected prospectively at a small island DGH on 89 patients from September 2018 - March 2020. Results: The 30-day readmission rate was 7.9% and the 90-day mortality rate was 0% locally. Six (86%) of the readmitted patients had a left-sided colorectal disease (potentially due to increased risk with a colo-colonic anastomosis). Five (71%) patients required return to theatre; four due to anastomotic leaks and one due to a wound collection. 43% of readmitted patients had upward white cell count/c-reactive protein (WCC/CRP) trends on discharge. Readmitted patients had a mean discharge CRP result of 150 (range 15.9 - 311). Conclusions: Colorectal surgery under ERAS at our institution is at a high standard stemming from effective staff education and post-operative patient counselling. This study provides evidence that WCC/CRP trend is related to postoperative prognosis.